PENGALAMAN PENGKONSUMSIAN HERBAL KUAH RUJAK PADA IBU NIFAS DI WILAYAH KOTA TERNATE - Suaib, Nurkila; Saraha, Rosida Hi (UPPM Politeknik Kesehatan Kemenkes Ternate, Maluku Utara, Indonesia, 2015)
Abstract : Our countrybecameone of the centersof medicinal plants inthe world. Thousands oftropicalplant species, thrivesthroughout the country. GenerallypeopleinNorth Malukucity of Ternateisespeciallythe people who stillholdsthe customs and habitsare hereditarymaintainedbythe local community. Ternatecitywitha tropicalclimatethat isovergrown withvariouskinds ofwild plantsthatgrow welland theplants thatgrowin thesettlementas seasoning, usedbyancestorsforhealthasherbalmedicine. Oneexample isa plant thatcomes fromsuchsettlementsSerei, ginger, galangal, turmeric, acid, palm sugar, coriander, pepperandherbsareprocessed intoKuahRujakasit can be usedonnew motherswhoare consideredbeneficialto theprocess of spendingthe remnantsproducts of conception(lochia). This research isa qualitativedescriptivecross sectionaltimeapproaches. Data was collected throughin-depthinterview techniques(Indepth Interview) in7new mothersaskey informants. Data analysisusing the method ofcontent analysis(content analysis). The results showed that postpartum mothers consumed in Ternate is all new mothers herbs salad dressing. All postpartum women interviewed have a way of processing, composition and dosage of herbal salad dressing and salad dressing herbal dose almost have in common. All postpartum women interviewed explained the perceived benefits after consuming herbal salad dressing on the puerperal period.The conclusionof this studyisbased onthe results,thatthe midwifebelievescultur(culture) andpostpartummaternal behaviorinTernate Cityis one ofthe techniquesinthetreatment ofpuerperium